2006
DOI: 10.1111/j.1745-7254.2006.00406.x
|View full text |Cite
|
Sign up to set email alerts
|

Caffeic acid ameliorates early and delayed brain injuries after focal cerebral ischemia in rats

Abstract: Aim: To investigate the effects of caffeic acid on early and delayed injuries after focal cerebral ischemia in rats, and the possible relation to 5-lipoxygenase inhibition. Methods: Transient focal cerebral ischemia was induced by middle cerebral artery occlusion in Sprague-Dawley rats. Caffeic acid (10 and 50 mg/kg) was ip injected for 5 d after ischemia. The brain injuries were observed, and the levels of cysteinyl leukotrienes and leukotriene B 4 in the brain tissue were measured. Results: Caffeic acid (50 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
44
0
2

Year Published

2009
2009
2015
2015

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 67 publications
(54 citation statements)
references
References 34 publications
5
44
0
2
Order By: Relevance
“…For example, CAPE/caffeic acid has been reported to protect the brain against induced diabetes, quinolinic acid-induced brain damage, aluminuminduced toxicity, neonatal hypoxia, and transient focal ischemia (Celik and Erdogan, 2008;Kalonia et al, 2009;Khan et al, 2007;Wei et al, 2004;Yang et al, 2008;Zhou et al, 2006). Caffeic acid has also been reported to reduce lesion area and glial scar formation following cryoinjury in mice (Zhang et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…For example, CAPE/caffeic acid has been reported to protect the brain against induced diabetes, quinolinic acid-induced brain damage, aluminuminduced toxicity, neonatal hypoxia, and transient focal ischemia (Celik and Erdogan, 2008;Kalonia et al, 2009;Khan et al, 2007;Wei et al, 2004;Yang et al, 2008;Zhou et al, 2006). Caffeic acid has also been reported to reduce lesion area and glial scar formation following cryoinjury in mice (Zhang et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…Ca 2ϩ is thought to facilitate binding of 5-LO to phosphatidylcholine on the nuclear membrane whereas ATP is thought to increase the 5-LO activity by stabilizing the protein structure through the C2-like domain (56). 5-LO inhibitors have been reported to improve cell survival, to protect against ischemia in vitro (61), and to be anti-inflammatory in vivo (74). The leukotrienes synthesized by 5-LO signal through at least two classes of G protein-coupled receptors, named cysteinyl leukotriene 1 (CysLT 1 ) and 2 (CysLT 2 ) receptors, which are widely expressed in cells of the immune system but in the case of CysLT 1 are also expressed in endothelial cells and the lung.…”
mentioning
confidence: 99%
“…Specifically, elevation of intracellular calcium that generally occurs after excitotoxicity and mitogen-activated protein kinase (MAPK)-regulated phosphorylation that can be induced by oxidative stress [3] both activate 5-LOX. Previously, we reported that 5-LOX can be activated after ischemic brain injury in rats [8,10] , after oxygen-glucose deprivation (OGD)-induced ischemic injury in cultured neurons and in pheochromocytoma (PC12) cells [11][12][13][14] . In primary neuron cultures, OGD induces release of excitatory amino acids that activate NMDA receptors to elevate intracellular calcium, resulting in 5-LOX translocation to the nuclear envelope and activation of 5-LOX to produce CysLTs [12] .…”
mentioning
confidence: 99%
“…5-LOX metabolites play an important role in inflammatory diseases of the peripheral tissues and the central nervous system, such as bronchial asthma [4,5] and ischemic brain injury [6][7][8][9] . In these diseases, various stimuli activate 5-LOX through two main ways.…”
mentioning
confidence: 99%